2011
DOI: 10.1007/s00167-011-1502-4
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of knee morphometrics using MRI and arthroscopy: a comparative study between ACL-injured and non-injured subjects

Abstract: There were differences in bony morphology between men and women and between subjects with and without ACL injury. The bony morphology that was different between ACL-injured and non-injured subjects varied between male and female subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 23 publications
4
61
2
Order By: Relevance
“…The majority of the studies used MRI7–17 19–21 23 24 or radiography7 18 21–23 25–29 for measurement of bone morphology parameters. Additionally, Vrooijink et al 12 compared their measurements performed by MRI or intraoperatively, which did not find any correlation. Most of the studies were retrospective case–control studies and their methods are described in table 2.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The majority of the studies used MRI7–17 19–21 23 24 or radiography7 18 21–23 25–29 for measurement of bone morphology parameters. Additionally, Vrooijink et al 12 compared their measurements performed by MRI or intraoperatively, which did not find any correlation. Most of the studies were retrospective case–control studies and their methods are described in table 2.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, one study performed a case-series of ACL-reconstructed and ACL-deficient patients 25. Overall, the studies provided a moderate description of their inclusion and exclusion criteria: 11 studies included isolated unilateral ACL tears,7 9 11 13 16 20–26 7 studies included ACL reconstruction/surgery patients,8 10 12 15 19 27 28 one study explored ACL-deficient knees,29 one study investigated the contralateral knee of ACL-injured patients17 and one study also included bilateral ACL tears 23. Nonetheless, 12 of 23 studies (52%)7–10 12 13 15–17 20 23 25 did not report how did they determined the status of ACL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bicondylar width also was quantified as a measure of overall knee size [58]. All the dimensions were measured using Onis TM Viewer 2.5 (DigitalCore, Tokyo, Japan) and Mimics 1 15 software (Materialise; Ann Arbor, MI, USA), and were reported in millimeters or degrees.…”
Section: Anatomic Indices Measurementmentioning
confidence: 99%
“…Studies have also shown that women have smaller notch sizes than men. This may lead to the assumption that the smaller notch possibly contributes to a higher frequency of ACL ruptures in women [14][15][16][17][18][19] . Lombardo et al [20] described that there is no differences between ACL-injured and non-injured basketball players with respect to Notch width.…”
Section: Discussionmentioning
confidence: 99%